Endangered words, threatened worlds: Sapara identity in dialogue with UNESCO - Rosado Valencia, Erika (Latin American and Caribbean Ethnic Studies, 2024)
This article explores the self-representation practices of the leaders of the Sapara Nationality of Ecuador in response to UNESCO’s cultural policies and the recognition of their oral traditions and cultural manifestations as Masterpieces of the Intangible Heritage of Humanity (2001). Through critical discourse analysis, the author elucidates how Sapara leaders’ identity narratives engage with UNESCO’s discourses on endangered languages. The analysis revolves around three linguistic ideologies strongly present in UNESCO’s discourses: the metonymic relation between language and territory, the co-occurrence between biological and cultural diversity and the objectification of language as a universal possession. The author argues that supranational institutions like UNESCO are influential in defining notions of indigenous ‘authenticity,’ to which Sapara leaders adapt, negotiate and resist.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Ecuador; indigeneity; intangible heritage; language ideology; Sapara; UNESCO

Inventing the savage: the Sapara people of the Ecuadorian Amazon in 19th-century travel writing - Rosado Valencia, Erika; Jansen, Silke; Gerique-Zipfel, Andres (Journal de la Société des américanistes, 2024)
In this article, we examine the discursive construction of the Sapara people of the Ecuadorian Amazon in the writings of travelers who explored the region in the second half of the 19th century. We focus mainly on the ways in which these writings reflect prevailing ideologies of the time, according to which “civilized” human societies could be distinguished from “savage” ones. In doing this, we analyze the representation of different aspects of the Sapara culture, such as agriculture and working habits, gender relations and sexual practices and the art of war and leisure. We frame our analysis in the theoretical proposal of Irvine and Gal for the ideological construction of cultural difference through the semiotic processes known as rhematization, fractal recursivity, and erasur
Keywords: Ecuadorian Amazon; cultural difference; 19th-century travel writing; semiotic approach; Sapara people; savagery

Inventing the savage: the Sapara people of the Ecuadorian Amazon in 19th-century travel writing L’invention du sauvage : le peuple sapara de l’Amazonie équatorienne dans les récits de voyage du XIXe siècle La invención del salvaje: el pueblo sapara de la Amazonía ecuatoriana en los relatos de viajes del siglo XIX - Rosado Valencia, Erika; Jansen, Silke; Gerique-Zipfel, Andres (Journal de la Société des américanistes, 2024)
In this article, we examine the discursive construction of the Sapara people of the Ecuadorian Amazon in the writings of travelers who explored the region in the second half of the 19th century. We focus mainly on the ways in which these writings reflect prevailing ideologies of the time, according to which “civilized” human societies could be distinguished from “savage” ones. In doing this, we analyze the representation of different aspects of the Sapara culture, such as agriculture and working habits, gender relations and sexual practices and the art of war and leisure. We frame our analysis in the theoretical proposal of Irvine and Gal for the ideological construction of cultural difference through the semiotic processes known as rhematization, fractal recursivity, and erasure.
CRIS-Team Scopus Importer:2025-02-04
Keywords: 19th-century travel writing; cultural difference; Ecuadorian Amazon; Sapara people; savagery; semiotic approach

When ‘civilized’ and ‘savage’ languages meet: Language Ideological Work in 19th Century Travel Accounts on the Ecuadorian Amazon - Jansen, Silke; Rosado Valencia, Erika (Journal of Postcolonial Linguistics, 2023)